Teaching the Evaluation of Female Pelvic Pain: A Hands-On Simulation to Reinforce Exam Skills and Introduce Transvaginal Ultrasound - Jennifer Pearson; Amy Greminger; Emily Onello; Sandy Stover (Association of American Medical Colleges, 2021)
Introduction Reproductive-age female patients commonly seek evaluation for pelvic pain in a variety of health care settings. Thus, teaching medical students how to effectively evaluate female pelvic pain is a necessary part of medical education. There are limited opportunities, however, to reinforce the needed skills for this common but sensitive presentation that can be anxiety-producing for preclinical students. Methods The case involved a 23-year-old female presenting with lower abdominal/pelvic pain. Students performed the necessary history, physical examination, cervical sampling, and transvaginal ultrasound evaluation to make the diagnosis of pelvic inflammatory disease (PID) complicated by a tubo-ovarian abscess. The 30-minute simulated patient encounter was followed by a 30-40 minute faculty-led debrief. Results This simulation case has been sustained in the curriculum since 2011 for 65 students per year. Through use of a faculty critical action checklist, debrief discussion, examination performance, and student evaluation feedback, this simulation has demonstrated effectiveness. Of students, 93 of 193 students (48%) who participated in the simulation case from 2018-2020 completed a survey in which they rated the degree of agreement with statements about the simulation based on a 5-point Likert Scale (1 = strongly disagree, 5 = strongly agree). All questions had a mean response of 4.5-4.8 in 2018-2020, demonstrating the consistent agreement by students of the clarity, fidelity, and knowledge-enhancing value of the simulation. Discussion This simulation provided a useful opportunity and a safe environment for preclinical medical students to acquire knowledge and skills necessary to evaluate a female patient with pelvic pain and PID.